Do the Morningness-Eveningness questionnaire and Munich ChronoType questionnaire change after morning light treatment? - Helen J. Burgess; Fumitaka Kikyo; Zerbrina Valdespino-Hayden; Muneer Rizvydeen; Momoko Kimura; Mark H. Pollack; Stevan E. Hobfoll; Kumar B. Rajan; Alyson K. Zalta; John W. Burns (Sleep Science and Practice, 2018)
Abstract ᅟ The Morningness-Eveningness Questionnaire (MEQ) and Munich ChronoType Questionnaire (MCTQ) are sometimes used to estimate circadian timing. However, it remains unclear if they can reflect a change in circadian timing after a light treatment. In this study, 31 participants (25–68 years) completed both questionnaires before and after a 13–28 day morning light treatment. The dim light melatonin onset (DLMO), a physiological marker of circadian timing, was also assessed in a subsample of 16 participants. The DLMO phase advanced on average by 47 min (p < 0.001). The MEQ score increased by 1.8 points (p = 0.046). The MSFsc measure derived from the MCTQ advanced by 8.7 min (p = 0.17). The shift towards morningness observed in both questionnaires correlated with the phase advance observed in the DLMO (MEQ r = − 0.46, p = 0.036; MSFsc r = 0.81, p < 0.001). Results suggest that these circadian questionnaires can change in response to a light treatment, indicating they can reflect underlying changes in circadian timing. Trial registration Clinicaltrials.gov NCT02373189 retrospectively registered 2/26/15; NCT03513848 retrospectively registered 5/2/18.